Predicting Why Women Have Elective Repeat Cesarean Deliveries and Predictors of Successful Vaginal Birth After Cesarean. Issue 2 (June 2015) - Mone, F.; Harrity, C.; Toner, B.; Mcnally, A.; Adams, B.; Currie, A.
<x xml:space="preserve">Abstract</x> (Int J Gynaecol Obstet. 2014;126(1):67–69)